KONFLIK PEMBANGUNAN PETERNAKAN AYAM DI KECAMATAN GUNUNG KENCANA - Dede Surya Lesmana; Aulia Prima Rahman Yunas; Naufal Syafiq Permana; Wahyu Kartiko Utami (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2020)
This study discusses the conflict that occurred in Ciakar Village, Gunung Kencana District due to the existence of a chicken farm in the middle of a community settlement. This conflict originated from the unrest of the surrounding community who considered the development of livestock that could be approved for environmental comfort, because it would cause a foul odor from chicken manure. The theory used in this study is the theory of social movements according to Jean Cohen which is supported by environmental political theory and conflict theory. The method used in this research is descriptive qualitative method. Collecting data in this study through interviews, observation, and study documents. The results of research that prove the conflict carried out by chickens that led to the transition of social movements conducted by the community to the government through the audience channel by collecting community ID cards that refused, then supported by a letter posted by the Gunung Kencana Student Association. The movement carried out by the community was attractive both by the government because the office negotiations had permits, office comfort offices, and Perda Regional Regulation No. 2 of 2014 concerning regional spatial plans (RTRW) and regional regulations No.9 of 2010 concerning licensing fees certain.